Enhancing Students Sustainability Literacy through a Green Economy-Based Project-Based Learning Model - Mulwandani, Zahra; Fajrina, Suci; Lufri; Fadilah, Muhyiatul (Bioilmi: Jurnal Pendidikan, 2024)
Sustainability literacy has emerged as a critical educational need, particularly in the context of global challenges such as climate change, natural resource management, and socio-economic issues. Despite its importance, a survey by UNESCO (2021) revealed that only 12% of students in Indonesia possess adequate sustainability literacy, indicating a significant gap in educational effectiveness. This study aims to investigate the impact of a green economy-based Project Based Learning (PjBL) model on enhancing students' sustainability literacy in biology at SMAN 1 Sungai Penuh. Employing a quasi-experimental design with a posttest-only control group, the research involved 72 high school students divided into an experimental group (36 students) and a control group (36 students). Data were collected using structured questionnaires to assess sustainability literacy before and after the intervention. The results demonstrated a significant improvement in the experimental group, with an average post-test score of 82.5 (SD = 5.1) compared to 65.3 (SD = 4.8) in the control group. Statistical analysis using a t-test confirmed the significance of these findings (t = 5.67, p < 0.01). The study concludes that implementing the green economy-based PjBL model effectively enhances students' understanding of sustainability concepts and promotes active engagement in learning, providing valuable insights for curriculum development focused on sustainability literacy.